Legal Protection for Urban Online-Transportation-Users’ Personal Data Disclosure in the Age of Digital Technology - Kukuh Tejomurti; Hernawan Hadi; Moch Najib Imanullah; Rachma Indriyani (Faculty of Law, Universitas Padjadjaran, 2018)
This study aims to describe the protection of personal data of online transportation customer from the perspective of legal protection for privacy. Although online transportation services enable users to travel with low-cost easily, they also pose new challenges. The challenges include the absence of standards of protection for both passengers and drivers, especially the protection of the user’s privacy rights. The issue of personal data protection and the privacy rights has arisen after some drivers intimidate their customers because thecustomers give bad ratings that the drivers do not desire. The types of intimidation are, among others, determining the work time, travel route, housecondition, workplacecondition, etc. Criminal individuals can expose all weaknesses in customers’ personal data protectionto commit acts of crime. In addition, the users’ personal data can be transferred to other parties outside the jurisdiction of Indonesian law. This study uses normative legal research with prescriptive character. The legal approach used in this study is the conceptual and the regulatory approaches. The results show that, until now, there is no guarantee of the protection of privacy rights for online transportation users. The consumers’ efforts to make legal remedies for compensation claims also face problems due to the existence of standard clauses in the provisions of the privacy policy.Perlindungan Hukum terhadap Pengguna Transportasi Daring terhadap Keamanan Privasi Data Pribadi DigitalAbstrakArtikel ini meneliti tentang bagaimana pemetaan keamanan data pribadi digital pelanggan moda transportasi online di Indonesia dalam perspektif perlindungan hukum atas privasi. Meski layanan moda transportasi online memudahkan pengguna untuk bepergian dengan tawaran tarif murah, namun moda transportasi daring berbasis aplikasi juga menimbulkan tantangan baru, yaitu belum adanya standar keamanan baik bagi penumpang maupun driver moda transportasi berbasis online, khususnya keamanan hak atas privasi data pribadi digital. Persoalan keamanan data pribadi sudah muncul mulai dari pelanggan yang diintimidasi oleh driver karena memberikan penilaian buruk, sms atau chat whatsapp yang tidak dikehendaki dari driver atau pihak ketiga lainnya, sampai pada mendeterminasi waktu berangkat kerja, rute perjalanan, kondisi rumah, kondisi tempat kerja. Semua kelemahan keamanan data pribadi pelanggan dapat dimanfaatkan oleh oknum kriminal untuk melakukan aksi kejahatan, bahkan penjualan data-data penting yang bersifat pribadi itu ke pihak lain. Hasil penelitian menunjukan bahwa sampai saat ini belum ada jaminan keamanan perlindungan hak atas privasi bagi pengguna transportasi daring dan upaya pengguna sebagai konsumen dalam melakukan upaya hukum gugatan ganti rugi juga menghadapi persoalan karena adanya standar klausula baku pada ketentuan kebijakan privasiDOI: https://doi.org/10.22304/pjih.v5n3.a5